2015
DOI: 10.1016/j.bjid.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of late presentation for HIV treatment in a reference center in Belo Horizonte, Southeastern Brazil, from 2008 to 2010

Abstract: The proportion of patients who were late attending a clinic for HIV treatment is still high, and effective strategies to improve early HIV detection with a special focus on the vulnerable population are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…In Brazil, research studies on late onset for the care with HIV infection published from 2011 to 2016 estimated prevalence rates ranging from 52.5% to 69.8% (14,(23)(24)(25)(26) . These results are below what is expected for consolidated public health programs for PLHIV, such as that of Brazil (24) .…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, research studies on late onset for the care with HIV infection published from 2011 to 2016 estimated prevalence rates ranging from 52.5% to 69.8% (14,(23)(24)(25)(26) . These results are below what is expected for consolidated public health programs for PLHIV, such as that of Brazil (24) .…”
Section: Discussionmentioning
confidence: 99%
“…In analyzing the medical records, we observed that, in some cases, the diagnosis for HIV occurred from the investigation and initial detection of this STI. A study carried out in Belo Horizonte indicated that individuals with syphilis were less likely to have late treatment/diagnosis of HIV (26) .…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of people who are diagnosed late and who show up late for care with HIV infection, observed in Brazil and other countries (3)(4)(5) , constitutes an emergency problem to be considered in the response to pandemic. This problem is configured as a complex and multifactorial phenomenon, which, in addition to being associated with sociodemographic (4)(5)(6) and sociocultural factors (7)(8) and referring to barriers of health services (9)(10) , relates to psychosocial aspects such as subjectivities and representations about HIV/AIDS that influence the search for diagnosis by vulnerable people (11) .…”
Section: Introductionmentioning
confidence: 99%